Stakeholder consultations and the legitimacy of regulatory decision‐making: A survey experiment in Belgium. Issue 3 (11th June 2020) - Beyers, Jan; Arras, Sarah
Abstract: Agencies consult extensively with stakeholders such as industry associations, nongovernmental organizations, and trade unions. One rationale for consultations is that these improve procedural legitimacy and lead to greater acceptance of regulatory outcomes by citizens and the regulated industry. While this presumption of a positive relation between stakeholder consultations and the legitimacy of agencies is widespread, research analyzing this relationship remains scarce. Using a survey experiment, we examine the effect of open and closed consultations on the acceptance of procedures and regulatory outcomes in the field of environmental politics. The results demonstrate that consultation arrangements positively affect the acceptance of decision‐making procedures, especially when regulators grant access to different types of stakeholders. However, although the consultation arrangement itself does not directly affect acceptance of the regulatory outcome, procedural legitimacy matters, as it increases decision acceptance among individuals who are negatively disposed toward government regulation.